Characterization of Amaranthus species: ability in nanoparticles fabrication and the antimicrobial activity against human pathogenic bacteria - Hassan, Walaa A.; Mohammed, Afrah E.; AlShaye, Najla A.; Sonbol, Hana; Alghamdi, Salma A.; Iamonico, Duilio; Korany, Shereen M. (PeerJ, 2024)
The present work aimed at differentiating five Amaranthus species from Saudi Arabia according to their morphology and the ability in nanoparticle formulation. Biogenic silver nanoparticles (AgNPs) were synthesized from leaf extracts of the five Amaranthus species and characterized by different techniques. Fourier-transform infrared spectroscopy (FT-IR) was used to identify the phyto-constituents of Amaranthus species. The nanoparticles (NPs) were characterized by UV-visible spectroscopy, dynamic light scattering (DLS), transmission electron microscopy (TEM), and energy-dispersive X-ray spectroscopy (EDX). The antibacterial activity of the synthesized NPs was tested against Staphylococcus aureus, E. coli, Klebsiella pneumoniae and Pseudomonas aeruginosa using the agar well diffusion method. Spherical NPs varying in size and functional groups from the five plant species were demonstrated by TEM, DLS and FTIR analysis, respectively. Variations in NPs characteristics could be related to the phytochemical composition of each Amaranthus species since they play a significant role in the reduction process. EDX confirmed the presence of Ag in plant fabricated AgNPs. Antibacterial activity varied among the species, possibly related to the NPs characteristics. Varied characteristics for the obtained AgNPs may reflect variations in the phytochemical composition type and concentration among Amaranthus species used for their fabrication.
Keywords: Amaranthus spp.; Taxonomy; Antimicrobial; Silver nanoparticles